A Systematic Review on Sex- and Gender-Sensitive Research in Public Mental Health During the First Wave of the COVID-19 Crisis - Tibubos, Ana N.; Otten, Daniëlle; Ernst, Mareike; Beutel, Manfred E. (Frontiers in Psychiatry, 2021)
Background Sex and gender are important modifiers of mental health and behavior in normal times and during crises. We investigated whether they were addressed by empirical, international research which explored the mental health and health behavior ramifications after the onset of the COVID-19 pandemic. Methods We systematically searched the databases PsyArXiv, PubMed, PsycInfo, Psyndex, PubPsych, Cochrane Library, and Web of Science for studies assessing mental health outcomes (main outcomes) as well as potential risk and protective health behavior (additional outcomes) up to July 2, 2020. Findings Most of the 80 publications fulfilling the selection criteria reflected the static difference perspective treating sex and gender as dichotomous variables. The focus was on internalizing disorders (especially anxiety and depression) burdening women in particular, while externalizing disorders were neglected. Sex- and gender-specific evaluation of mental health care use has also been lacking. With respect to unfavorable health behavior in terms of adherence to prescribed protective measures, men constitute a risk group. Interpretations Women remain a vulnerable group burdened by multiple stresses and mental health symptoms. The neglect of sex and gender-specific evaluation of aggression-related disorders, substance addiction, and mental health care use in the early stage represents a potentially dangerous oversight.